Migration as a risk and a livelihood strategy: HIV across the life course of migrant families in India - Rai, T; Lambert, H; Ward, H (Taylor and Francis, 2016)
Migrant workers are understood to be vulnerable to HIV. However, little is known about the experience of migration-based households following HIV infection. This qualitative study examined the migration-HIV relationship beyond the point of infection, looking at how it affects livelihood choices, household relationships and the economic viability of migrant families. We conducted semi-structured interviews with 33 HIV-positive migrant men and women recruited from an anti-retroviral therapy (ART) centre in north India. Following infection among the migrant men, contact with free, public-sector HIV services was often made late, after the development of debilitating symptoms, abandonment of migrant work and return to native villages. After enrolment at the ART centre participants’ health eventually stabilised but they now faced serious economic debt, an inflexible treatment regimen and reduced physical strength. Insecure migrant job markets, monthly drug collection and discriminatory employment policies impeded future migration plans. HIV-positive wives of migrants occupied an insecure position in the rural marital household that depended on their husbands’ health and presence of children. The migration-HIV relationship continued to shape the life course of migrant families beyond the point of infection, often exposing them again to the economic insecurity that migration had helped to overcome, threatening their long-term survival.